Peningkatan Kesadaran Lingkungan dan Literasi Sosial Masyarakat melalui Program KKN Tematik di RT 02 RW 01 Kelurahan Sawah Lebar Kota Bengkulu Tahun 2025 - Mayzan Dwi Yusandi; Rika Hayati; Tiara Desri Meisena; M. Sihab; Riska Ayuni Saputri; Ahmad Asyhari; Asnawati Asnawati; Karona Cahya Susena (Universitas Dehasen Bengkulu, 2026)
The Thematic Community Service Program (Kuliah Kerja Nyata Tematik/KKN-T) is a form of community engagement aimed at enhancing social, environmental, and educational awareness within the community. This program was implemented in RT 02 RW 01, Sawah Lebar Sub-district, Ratu Agung District, Bengkulu City. The identified issues included low environmental management awareness, limited educational activities for children, and underutilization of the surrounding community spaces. The methods applied in this program consisted of observation, participatory approaches, direct education, and community-based practical activities. The implemented programs included environmental cleanliness socialization, learning assistance for children, health exercise activities, and the utilization of recycled materials as environmental education media. The results indicated increased community participation, improved awareness of environmental cleanliness, and enhanced learning motivation among children. This KKN-T program is expected to provide sustainable positive impacts and strengthen the role of students as agents of change in the community